Imido‐Supported Borohydrides of Titanium, Vanadium and Molybdenum. Issue 12 (4th February 2013) - Khalimon, Andrey Y.; Peterson, Erik; Lorber, Christian; Kuzmina, Lyudmila G.; Howard, Judith A. K.; van der Est, Art; Nikonov, Georgii I.
Abstract: New imido bis(borohydride) complexes [(RN=)M(PMe3 )2 (η 2 ‐BH4 )2 ] [R = Ar, M = Ti (3 ); R = Ar, M = V (5 ); R = Ar, M = Mo (6 ); R = Ar′, M = Mo (7 ); Ar = 2, 6‐ i Pr2 C6 H3, Ar′ = 2, 6‐Me2 C6 H3 ] were prepared by the reaction of dichlorides [(RN=)MCl2 (PMe3 ) n ] (M = Ti, n = 2; M = V, n = 2, M = Mo, n = 3) with LiBH4 (2 equiv) in THF. Compounds3, 5, 6 and7 were studied by IR spectroscopy and X‐ray diffraction, and an EPR spectroscopy study was performed for paramagnetic compound5 . In3, the two borohydride units are orthogonal to each other as a result of the overlap of an antiphase combination of B–H orbitals with the empty d xy orbital of Ti. In contrast, the d xy orbital of the metal atom is singly occupied in5 and fully occupied in6 and7, and both borohydride ligands are oriented in the same way, with the B(μ‐H2 )M moieties orthogonal to the P–M–P vector. Abstract : Treatment of (imido)Ti, ‐V and ‐Mo dichloride complexes with LiBH4 gives imido bis(borohydride) complexes, which have been studied by NMR and EPR spectroscopy, and X‐ray diffraction.